Arthroscopic pull-through suture for tibial eminence avulsion fracture: a case series - Simatupang, Mario D.; Aryana, I. G. N. Wien; Nugraha, Hans K. (International Journal of Research in Medical Sciences, 2020)
Fractures of the tibial eminence is commonly reported in adolescents and adults, due to traffic accident, sports injury, or any other mechanism. Case 1: a 12-year-old male complained knee pain after a traffic accident 2 months prior to visit. Case 2: a 31-year-old female complained knee pain which worsened with long-distance walking and sitting, after falling on her knees one month prior to visit. Case 3: a 27-year-old female complained a worsening knee pain after traffic accident 12 years ago. Although it has been extensively studied, controversies regarding the best fixation method still exist. Open technique was once popular, but some morbidity has been associated with this method. Therefore, a new approach using arthroscopic pull-through suture technique, albeit technically challenging, is currently being advocated as a treatment option for such fractures. The result in our series confirm that all of 3 patients have a good result based on international knee documentation committee (IKDC) scoring for evaluation the treatment, hence support the use of this novel technique for the patients with tibial eminence avulsion fracture.